Modulating superabsorbent polymer properties by adjusting the amphiphilicity - Stocker, Craig W.; Lin, Maoqi; Wong, Vanessa N. L.; Patti, Antonio F.; Garnier, Gil (Frontiers in Chemistry, 2022)
The role of amphiphilicity in polysaccharide-based superabsorbent polymers is paramount in determining material properties. While the performance of freeze-dried polymers is improved by maximizing hydrophilicity, this may not be the case for evaporative-dried polymers. In this study, four diglycidyl ether crosslinkers, with varying chain lengths and amphiphilicities, were used to synthesize a series of evaporative-dried carboxymethyl cellulose-based superabsorbent films. Through structural and physiochemical characterization, the effect of amphiphilicity on swelling and mechanical properties was established. Contrary to freeze-dried polymers, it was found that the addition of hydrophobic moieties by crosslinking with novel poly(propylene glycol) diglycidyl ether crosslinkers increased the swelling performance of evaporative-dried polymers. By adding hydrophobic functional groups, a reduction in inter-chain hydrogen bonding occurs during evaporative-drying, reducing the degree of hornification and decreasing the entropy requirement for water uptake. By optimizing the amphiphilic ratio, a poly(propylene glycol)-carboxymethyl cellulose polymer achieved a swelling capacity of 182 g/g which is competitive with freeze-dried cellulose-based hydrogels. The mechanical properties of these films improved with the addition of the crosslinkers, with glycerol-carboxymethyl cellulose polymers achieving a tensile strength of 39 MPa and a Young’s Modulus of 4.0 GPa, indicating their potential application as low-cost, swellable films.